The Impact of AI Usage in Supporting English Literature Students’ Learning (2022) - Fahira, Ayuke Nurul; Siagian, Chyntia Riquella; Simarmata, Deniela Yoshelyn; Manik, Sinta Fransiska; Natsir, Muhammad (CV. Rayyan Dwi Bharata, 2025)
This study investigates the impact of artificial intelligence (AI) tools on English Literature students’ learning experiences. Using a quantitative approach with a structured survey, 22 students from Universitas Negeri Medan were examined regarding their frequency of AI usage, purposes, and perceptions of its impact on academic skills. The findings indicate that AI tools are predominantly used for essay writing, grammar correction, idea generation, and translation. Most students reported improved comprehension, enhanced writing skills, and increased confidence in English usage. However, concerns about dependency and the accuracy of AI outputs were also raised. While 50% of students admitted to being somewhat dependent on AI tools, a majority (54.5%) found them effective in improving overall academic performance. The study underscores the dual role of AI in education—providing efficiency and support while posing challenges to creativity and critical thinking. The results highlight the importance of a balanced approach to integrating AI in academic settings.